Charlotte Bronte's Jane Eyre - Milton, Joyce (Woodbury, N.Y. Barron's, 1984)
A guide to reading "Jane Eyre" with a critical and appreciative mind. Includes background on the author's life and times, sample tests, term paper suggestions, and a reading list.1
Spine title: Bronte?'s Jane Eyre.
Bibliography: p. 111-113.
Keywords: Bronte, Charlotte -- 1816-1855. -- Examinations -- Study guides. 0.; Bronte, Charlotte -- 1816-1855.; Governesses in literature; English literature -- History and criticism